Kekuasaan Politik dan Adat Para Mosalaki di Desa Nggela dan Tenda, Kabupaten Ende, Flores - J. Emmed M. Prioharyono (Antropologi Indonesia, 2012)
This article discusses the relevance of applying the concepts of source of origin and system of precedence, that provide legitimacy for the Mosalaki of Lio in their construction and production as well as reproduction of power in everyday life, especially in their traditional political system. The data analyzed in this article is the result of fieldwork undertaken in the villages of Nggela and Tenda, District of Wolojita, the Regency of Ende Lio, Flores, with qualitative methods, specifically through the techniques of in-depth interviews and participant observation. The Mosalakis, as a matter of a fact, dominate the traditional political system as rulers of adat and adat land. Their practices of power are manifested mainly in ritual activities and the management of traditional land rights. The legitimated rights are transmitted through patrilineal descent, and is based upon source of origin and system of precedence, that are embeded in Lio culture. Key-words: source of origin, system of precedence, traditional political system, reproduction of power